2017
DOI: 10.1111/1750-3841.13757
|View full text |Cite
|
Sign up to set email alerts
|

A Cherry Seed‐Derived Spice, Mahleb, is Recognized by Anti‐Almond Antibodies Including Almond‐Allergic Patient IgE

Abstract: There are a number of examples of immunologic cross-reactivity elicited by pollens, fruits, seeds, and nuts of closely related plant species. Such cross-reactivity is of particular concern for patients with food allergies. In this report, we investigated a spice (mahleb) that is prepared from the kernel of the St. Lucie cherry, Prunus mahaleb, for cross-reactivity with almond (Prunus dulcis), using enzyme-linked immunosorbent assay (ELISA) and Western blot. Almond and mahleb are members of the same genus. Cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…A recent investigation showed a cherry seed-derived spice, mahleb , is recognized by anti-almond antibodies including almond-allergic patient IgE [ 25 ]. The cross-reactivity between almond and mahleb , which is prepared from the kernels of a species of cherry, should be of particular concern to almond-allergic patients and attending medical personnel.…”
Section: Prevalencementioning
confidence: 99%
“…A recent investigation showed a cherry seed-derived spice, mahleb , is recognized by anti-almond antibodies including almond-allergic patient IgE [ 25 ]. The cross-reactivity between almond and mahleb , which is prepared from the kernels of a species of cherry, should be of particular concern to almond-allergic patients and attending medical personnel.…”
Section: Prevalencementioning
confidence: 99%
“…Consequently, patients sensitive to almond amandin may experience adverse reactions upon exposure to foods (for example, persipan) containing the homologous peach protein. We have recently reported cross‐reactivity of almond allergic patients’ serum IgE with P. mahaleb 11S legumin (Noble and others ). Currently, there is no analytical method available for peach or cherry kernel protein detection.…”
Section: Resultsmentioning
confidence: 90%
“…This later interpretation is not incongruous with the findings of Noble et al, who have shown that IgE present in the serum of an almond allergic individual exhibited reactivity with mahaleb, both in ELISA and in Western Blot, though in their analysis, the authors were able to show competitive binding of antibody against both targets. 13 However, cross-reactivity with nut allergens is frequently observed in the context of birch pollen allergy, 1 and elevated serum levels of birch pollen-specific immunoglobulin IgE are reported for individuals with oralallergy syndrome towards plant-derived proteins. 14 Importantly, the results of this study do not preclude the possibility of cross-reactivity as it is important to consider that the nut extracts used for the SPTs were prepared from apparent raw nut materials, and it remains plausible that roasted nut extracts would have elicited different outcomes.…”
Section: Discussionmentioning
confidence: 99%